Students' Science Process Skills in Virtual Practicum in Science Learning - Nahdiati; Rabiatul Khairiyah; Nur Inayah Syar; Latifah Alimuninggar (International Conference on Elementary Education, 2023)
Online learning system causes students and lecturers to be capable of implementing long distance learning. By the presence of this system then there must be an alternative of science practicum through online in the laboratory. However, it does not guarantee the students to be capable of obtaining the whole knowledge and skill. The purpose of this research was to find out the implementation of virtual practicum method using PhET simulation on the skill of students’ science process in style and movement practicum. The method used in this research was qualitative descriptive applied on students of Madrasah Ibtidaiyah Teacher Education Study Program in the amount of 38 students. The techniques of data collection used in this research were observation and interview. Based on the data obtained, then the indicators of science process skill which could run well during the virtual practicum were observation, conducting communication, planning the experiment, and using the tool, material, and source. Overall the result of virtual practicum method implementation assisted by PhET simulation in science learning was in quite good category.